Software Requirements Specification Of Database Roads And Bridges In East Java Province Based On Geographic Information System - Dwanoko, Yoyok Seby (PROCEEDING IC-ITECHS 2014, 2014)
Database of Road and Bridge-based Geographic Information System (DJJ-SIG) isresented in this paper is a system designed to manage data and information across the roads and bridges in East Java that is used by the government as the information society. In essence, DJJ-SIG allows users who have access rights to view, add, edit and delete data roads and bridges that can be managed online dynamic web based. DJJ-SIG to manage the data that consists of identifying track roads, general data, the data segment and the data bridge traversed every road. This paper presents a software requirement Specification which is based on the needs of users are involved in the system with a case study in Dinas Bina Marga East Java.